PELATIHAN “FIND MY DREAM” DALAM PERSPEKTIF PSIKOLOGI PERKEMBANGAN: UPAYA MENINGKATKAN EFIKASI DIRI PENGAMBILAN KEPUTUSAN KARIR REMAJA - Riza Fitriana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effectiveness of the “Find My Dream” career planning training program from a developmental psychology perspective as an effort to improve career decision-making self-efficacy in adolescents. The research subjects consisted of 15 ninth-grade students from SMP X Pekanbaru who were selected using purposive sampling based on the criteria of not having a clear career choice, having doubts about determining their future education and employment, and being willing to participate in the entire training program. The research used a quantitative approach with a quasi-experimental design of the one-group pretest-posttest-follow-up type. Measurements were taken using a career decision-making self-efficacy scale at three stages: before training (pretest), after training (posttest), and three weeks after training (follow-up). The intervention provided was a career planning training program called “Find My Dream,” which was developed based on career planning theory components and took into account adolescent developmental characteristics. The normality test results showed that the pretest data were not normally distributed (p=0.038), while the posttest (p=0.164) and follow-up (p=0.590) data were normally distributed. Therefore, the analysis was continued using the Wilcoxon test, which showed an Asymp. Sig. (2-tailed) value of 0.001 (p<0.05), meaning that there was a significant increase in career decision-making self-efficacy after the training. Descriptively, self-efficacy scores also increased from pretest to posttest and remained stable until the follow-up stage, thus changing the category from low and moderate to high in most participants. These findings indicate that the “Find My Dream” training is effective as a developmental psychology-based intervention to improve adolescents' career decision-making self-efficacy.